Gay, Lesbian, and Bisexual (LGB) peoples' leadership self-effectiveness: The roles of internalized sexual stigma, LGB positive identity, and traditional masculinity - Salvati, Marco; Sari, Tunahan; Pellegrini, Valerio; De Cristofaro, Valeria (Frontiers in Sociology, 2023)
Grounded in the theoretical frameworks of the minority stress model and the model of positive identity in sexual minority people, the current research contributes to fill a gap in the previous literature, investigating the relationships among leadership self-effectiveness, internalized sexual stigma, positive identity, and adherence to traditional masculinity of gay, lesbian, and bisexual (LGB) individuals. Through a correlational study (N=449), we collected data from 229 gay/bisexual men (51%) and 220 lesbian/bisexual women (49%). We hypothesized that lower internalized sexual stigma, higher LGB positive identity, and higher adherence to traditional masculinity were associated to higher self-perceived effectiveness. The interactive relationships among the variables, including participants’ gender, were investigated from an exploratory perspective. The hypotheses were tested through two moderated regression models and the results confirmed that participants with lower internalized sexual stigma and higher LGB positive identity were more likely to perceive themselves as potential effective leaders. Also, the results showed a significant interaction between participants’ gender and traditional masculinity score suggesting that high adherence to traditional masculinity was a significant predictor of self-perceived effectiveness only for gay/bisexual men, but not for lesbian/bisexual women. This research contributes to provide both confirmation and novel insights into the key role of relevant factors impacting on LGB people’s leadership self-effectiveness, which might contribute to preserve the gay glass ceiling effect. The presence of antidiscrimination policies in organizations not only might reduce reports of discrimination but also enhance LGB employees' positive sense of self, which is a critical aspect to emerge as a leader.